(untitled) (Plant Tissue Culture and Biotechnology, 2019)
De-husked rice of four rice varieties viz., Iratom24, BRRI dhan 58, BRRI dhan 62 and Binnatoa was used to observe their regeneration efficacy and produce somaclones. MS supplemented with different combinations of plant growth regulators; MS + 2,4-D + BAP + NAA, MS + BAP + NAA + Kn + IAA and MS + IBA were used for callus induction, shoot regeneration and root induction, respectively. Transcendent frequency of callus was obtained in BRRI dhan58 (80.95%). MS supplemented with 1.5 mg/l 2, 4-D + 0.5 mg/l BAP + 0.5 mg/l NAA was found as the best for callus induction in BRRI dhan58. Maximum nutrient of shoot was found in BRRI dhan62 (80%) followed by BRRI dhan58 (66.66%). For shoot regeneration, MS supplemented with 1.5 mg/l BAP + 0.5 mg/l NAA + 0.5 mg/l Kn + 0.5 mg/l IAA performed better compared to other growth regulator combinations were tested. The highest numbers of roots were produced in all varieties under MS + 0.5 mg/l IBA media. BRRI dhan58 showed maximum number of plants was established at field condition after hardening. A total of 11, 17, 5 and 3 tissue derived plants was established in filed condition from Iratom24, BRRI dhan58, BRRI dhan62 and Binnatoa, respectively. Among the tissue culture variants, the variant number 36 derived from Binnatoa had the highest Fe 26.93 and 21.51 mg/l and Zn 42.67 and 38.84 mg/l contents in brown and polished rice grain, respectively. This high iron coupled with zinc content rice line could be the potential breeding material for developing Fe and Zn enriched rice cultivar.